Favorite Characters of Malay Folklores According to Students' Choices through Learning Using Canva Media - Ansit, Muhammad Najwan; Norli, Muhammad Asyraf (Raja Zulkarnain Education Foundation, 2025)
Among the 19 folklore titles in the Malay folklore book 'Patahnya Gunung Daik: Kumpulan Cerita Rakyat Kepulauan Riau' there is one folklore entitled 'Apek Weng Thai' which tells the life journey of a skilled young man in the kuntao martial arts association on Lingga Island which was then the center of government of the Riau-Lingga Sultanate in the past. In addition to the young man's character, there is also a figure of a Chinese ethnic kuntao martial arts teacher and a warrior in the Indragiri region. This study aims to describe: 1) the favorite character of the 'Apek Wrng Thai' folklore according to students' choices through learning using Canva media; 2) the similarity of the favorite character of the 'Apek Wrng Thai' folklore according to students' choices through learning using Canva media per sample group. This descriptive-quantitative research was conducted in 2024 at Sekolah Kebangsaan Sahabat 4, Lahat Datu District, Sabah, Malaysia, and Sekolah Kebangsaan Terusan Sugut, Beluran District, Sabah, Malaysia. The population of this study was 5th-gradeth-grade students who answered verbal questions in a questionnaire read by the teacher about their favorite character in the folk tale 'Apek Wen.'Thai'. There were 30 students from Lahat Datu and 28 students from Beluran. This study used a total sample. The research data were analyzed using descriptive statistical procedures, namely frequency and percentage. The results of the study: 1) the favorite character in the folk tale 'Apek Weng Thai' according to students' choices through learning using Canva media is Mahmud; 2) the favorite character in the folk tale 'Apek Wrng Thai' according to students' choices through learning using Canva media per sample group is not the same. The favorite character in the Lahat Datu sample group is Apeh Weng Thai, but the favorite character in the Lahat Datu sample group is Mahmud.